2020
DOI: 10.1186/s12885-020-06923-0
|View full text |Cite
|
Sign up to set email alerts
|

Black patients referred to a lung cancer screening program experience lower rates of screening and longer time to follow-up

Abstract: Background: Racial disparities are well-documented in preventive cancer care, but they have not been fully explored in the context of lung cancer screening. We sought to explore racial differences in lung cancer screening outcomes within a lung cancer screening program (LCSP) at our urban academic medical center including differences in baseline low-dose computed tomography (LDCT) results, time to follow-up, adherence, as well as return to annual screening after additional imaging, loss to follow-up, and cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 40 publications
6
57
0
Order By: Relevance
“…Several single-institution studies have found comparably low estimates of adherence after initial negative examination results, ranging from 18% to 51%. 13 , 14 , 17 This seemingly wide variation is explained in part by the use of different definitions of adherence across studies, with the lowest estimate based on a second screening within 11 to 13 months and the highest estimate based on a second screening within 18 months. 13 , 14 Nevertheless, others have reported higher estimates of adherence, up to 82%, when defining adherence as return for LDCT screening within 15 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several single-institution studies have found comparably low estimates of adherence after initial negative examination results, ranging from 18% to 51%. 13 , 14 , 17 This seemingly wide variation is explained in part by the use of different definitions of adherence across studies, with the lowest estimate based on a second screening within 11 to 13 months and the highest estimate based on a second screening within 18 months. 13 , 14 Nevertheless, others have reported higher estimates of adherence, up to 82%, when defining adherence as return for LDCT screening within 15 months.…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 14 , 17 This seemingly wide variation is explained in part by the use of different definitions of adherence across studies, with the lowest estimate based on a second screening within 11 to 13 months and the highest estimate based on a second screening within 18 months. 13 , 14 Nevertheless, others have reported higher estimates of adherence, up to 82%, when defining adherence as return for LDCT screening within 15 months. 12 , 15 , 16 A common feature of these studies showing higher adherence is a centralized program with a dedicated program coordinator to support tracking and follow-up of screened individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the clear survival benefit of LDCT screening in appropriate patients, there has been a relatively low adherence to these guidelines in clinical practice (8)(9)(10). In addition, several studies have described disparities in the use of LDCT screening in underserved populations, including racial/ethnic minorities (11,12), those living in rural areas with more limited access to care (13), and other vulnerable populations (14,15). Efforts to understand disparities in LDCT screening and their contributing factors have become increasingly relevant, as previous studies have shown that these same underserved populations have a greater incidence of lung cancer and are less likely to receive appropriate treatment (16)(17)(18)(19).…”
Section: Review Articlementioning
confidence: 99%
“…A retrospective study by Richmond et al (2020) examined LDCT screening rates at a community health center in North Carolina and found that eligible black patients were less likely to receive LDCT screening than white patients ( Richmond et al, 2020 ). A historical cohort study on lung cancer screening outcomes, including LDCT utilization rates, found that black patients were significantly less likely to receive LDCT compared to white patients, even when lung cancer screening status and neighborhood-level factors such as unemployment, education level, and income level were controlled ( Lake et al, 2020 ). Lung cancer screening using LDCT in a Medicare fee-for-service population was examined in a cross-sectional observational study by Tailor et al (2020) .…”
mentioning
confidence: 99%